PRESIDENT'S PAGE. Amy Blevins, Medical Library Association President, 2023-2024. - Kiscaden, Elizabeth; Craven, Hannah J.; Rios, Gabriel R.; Harris, Ryan; Nicholson, Joey (Journal of the Medical Library Association, 2025)
Amy Blevins served as the Medical Library Association president from 2023-2024. In this presidential biography, the authors outline a history of Blevins' recruitment to the career, career development, and impact on the association and the profession.